Experimental Study on Electromagnetic Metal Forming (EMF) - Taha Raad Al-Shaikhli, Badrul Hisham Ahmad, Malik Hasan Al-Taweel (International Journal of Advanced Science and Technology, 2020)
Electromagnetic forming (EMF) is a non-contact forming technique.  It is an impulse or high-speed formation process by applying Lorentz's forces to a workpiece that is ideally made from highly electrically conductive material without medium and mechanical contact in the workpiece. Hollow profiles, as well as 2D or 3D sheets can be formed, joined or split, can also be compressed or extended. Compared to conventional methods, the electromagnetic formation system has very high strain level and frequency. For several materials, the Forming limits can be extended. The state of the art of electromagnetic forming is discussed in this paper, according to the following aspects-Research on parameters related to actuating load, workpiece deformation, interaction between load parameters and workpiece deformation. Product behaviour, energy exchange during the process and research on the electrical formation theory and implementation. Based on this study, it is suggested why electromagnetic formation in industrial manufacturing processes has not been commonly undertaken so far and how the obstacles for its broad implementations can be faced.